2015
DOI: 10.1121/1.4921280
|View full text |Cite
|
Sign up to set email alerts
|

Non-song social call bouts of migrating humpback whales

Abstract: The use of stereotyped calls within structured bouts has been described for a number of species and may increase the information potential of call repertoires. Humpback whales produce a repertoire of social calls, although little is known about the complexity or function of these calls. In this study, digital acoustic tag recordings were used to investigate social call use within bouts, the use of bouts across different social contexts, and whether particular call type combinations were favored. Call order wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 46 publications
(91 reference statements)
5
36
0
Order By: Relevance
“…) and often produced in bouts containing the same or other call types (Rekdahl et al . ). Wops occurred commonly in the social call repertoire of the eastern Australian population (Dunlop et al .…”
Section: Descriptive Statistics Of Call Types (Mean ± Sd) From Humpbamentioning
confidence: 97%
“…) and often produced in bouts containing the same or other call types (Rekdahl et al . ). Wops occurred commonly in the social call repertoire of the eastern Australian population (Dunlop et al .…”
Section: Descriptive Statistics Of Call Types (Mean ± Sd) From Humpbamentioning
confidence: 97%
“…The sounds of humpback whales have been studied extensively in Alaska [121][122][123], off the eastern USA [124], at low latitudes [125][126][127][128][129], off eastern Australia [130][131][132][133][134][135][136] and off Antarctica [137].…”
Section: Megaptera Novaeangliae-humpback Whalementioning
confidence: 99%
“…Source levels of all types of social sounds range from 123 to 192 dB re 1 µPa rms @ 1 m [122,130]. A 3-year study off the east coast of Australia found 34 different sound types [131], either as single sounds or in bouts [133]. However, only a small subset of these sound types remain in the repertoire over time [134], meaning that the sound catalogue is highly variable and constantly changing.…”
Section: Megaptera Novaeangliae-humpback Whalementioning
confidence: 99%
“…Humpback non-song vocalization types have also been characterized and examined in several different ocean regions and in several different contexts. They include social sounds either vocalized or generated via surface activities, signals for coordinated movement during feeding and migration, as well as nighttime communication [1,2,[21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%